Using Conjoint Analysis to Predict the Launch Price of a New Smartphone - Samuel Tarigan (The Indonesian Institute of Science and Technology Research, 2023)
This study aims to identify the pricing strategy used by a premium smartphone manufacturer when launching a new type by comparing actual price predictions with price predictions using a rating-based conjoint analysis method. The results of an analysis of 172 respondents from a university in Indonesia showed that the manufacturer use a combination of a skimming strategy, using product variants that are similar to types known to users beforehand, and a penetrating strategy through product variants that have never existed before. Analysis of respondents' evaluation of five smartphone attributes also shows that the feature that has the most part worth and the highest importance is network technology (5G or 4G) followed by internal memory capacity. The manufacturer in the US has set prices that reflect part worths that are in line with RBCA prediction. In contrast, the distributor in Indonesia has set highest importance on the number of cameras. Managerially, these findings can be used by other smartphone manufacturers and distributors to when setting prices for future new products based on customer values. Theoretically, these findings indicate a significant difference between the conjoint analysis results and the producers' decisions that must be explained in the following research.